DAVID HUME'S EMPIRICISM AND ITS IMPLICATIONS FOR THE EPISTEMOLOGY OF ISLAMIC EDUCATION - Iefone Habiba; Dian Sidik Kurniawan; Zulfa Khairiah Ali; Muhammad Ihsan Siregar; Maragustam Siregar (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2026)
This study critically examines David Hume's (1711–1776) empiricist methodology and its implications for the epistemology of Islamic education. Hume's empiricism posits sensory experience as the sole valid source of knowledge, articulated through four primary pillars: the impressions–ideas dichotomy, critique of dogmatic causality, rejection of metaphysical substance, and systematic skepticism. This research aims to: (1) comprehensively analyze the core concepts of Hume's empiricist methodology; (2) identify its epistemological relevance and limitations within the Islamic educational framework; and (3) examine its application as a methodological instrument for analyzing Islamic pedagogical practice. A qualitative approach employing library research and descriptive-analytical methods was applied to primary and secondary sources. Findings indicate that, methodologically, Hume's empiricist principles are relevant for reinforcing experiential learning, observation-based evaluative culture, and critical inquiry into causal assumptions in educational practice. Concrete applications include simulation-based moral learning, empirical evaluation of sorogan and bandongan methods in pesantren, and the strengthening of tafakkur and muhasabah traditions as Islamic counterparts to methodological skepticism. However, epistemologically, Hume's empiricism cannot be wholly accepted, as its reduction of knowledge to sensory experience conflicts with Islamic epistemology, which upholds divine revelation as an autonomous and transcendent source of truth. A critical integration of both frameworks enables a rational, contextual, and evaluative Islamic education without abandoning its theological foundations. The implications of this study are twofold: theoretically, it offers a methodological bridge for reading Western epistemological traditions through an Islamic lens without compromising revelation as the primary source of truth; practically, it provides educators and curriculum designers with a concrete framework for embedding experiential, observation-based, and reflective practices into Islamic pedagogy, thereby strengthening the evaluative culture of pesantren and madrasah-based learning while preserving its theological integrity.